2010
DOI: 10.1186/1471-2105-11-372
|View full text |Cite
|
Sign up to set email alerts
|

Beyond co-localization: inferring spatial interactions between sub-cellular structures from microscopy images

Abstract: BackgroundSub-cellular structures interact in numerous direct and indirect ways in order to fulfill cellular functions. While direct molecular interactions crucially depend on spatial proximity, other interactions typically result in spatial correlations between the interacting structures. Such correlations are the target of microscopy-based co-localization analysis, which can provide hints of potential interactions. Two complementary approaches to co-localization analysis can be distinguished: intensity corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
121
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 15 publications
3
121
0
Order By: Relevance
“…Because the images in STORM data represent a reconstruction of locations and localization uncertainties of individual molecules, the overlap of signal in images is not the best method for determining whether molecules colocalize. Instead, we used a nearest-neighbor analysis to determine how close each point source is to its nearest neighbor by using the "strength" metric (69,70). Supporting the hypothesis of microdomain mixing, we found that, upon Snx1/2 depletion, the interaction strength between RME-8 and Hrs increased significantly [3.33 (n = 3) compared with 1.13 (n = 3) for control; P < 0.02, t test; Fig.…”
Section: Not All Retromer Associated Proteins Are Important For Domainmentioning
confidence: 99%
“…Because the images in STORM data represent a reconstruction of locations and localization uncertainties of individual molecules, the overlap of signal in images is not the best method for determining whether molecules colocalize. Instead, we used a nearest-neighbor analysis to determine how close each point source is to its nearest neighbor by using the "strength" metric (69,70). Supporting the hypothesis of microdomain mixing, we found that, upon Snx1/2 depletion, the interaction strength between RME-8 and Hrs increased significantly [3.33 (n = 3) compared with 1.13 (n = 3) for control; P < 0.02, t test; Fig.…”
Section: Not All Retromer Associated Proteins Are Important For Domainmentioning
confidence: 99%
“…In this case, multiple appearance of the same probe does not influence the cross-correlation curve, making analysis and interpretation easier. Spatial co-organization and co-localization of proteins can also be quantified by determining an "interaction potential" that is most likely to lead to the observed distribution of point localizations [36,37].…”
Section: Artificial Clustering and Over-countingmentioning
confidence: 99%
“…There, intracellular structures such as endosomes, vesicles, mitochondria, or viruses are labeled with fluorescent dyes and imaged over time with a confocal microscope. Many biological studies start from analyzing the dynamics of those structures and extracting parameters that characterize their behavior, such as average velocity, instantaneous velocity, spatial distribution [19,20], motion correlations, etc.…”
Section: Resultsmentioning
confidence: 99%